An S–O–R Model Analysis: The Role of Influencer Persona Attributes and Credibility in Shaping Food Purchase Intentions - Aldida Ramadhan; Kurniawati Kurniawati; Renny Risqiani (STIE Amkop Makassar, 2026)
This study was motivated by the crisis of consumer trust in the influence of food purchasing intentions on social media, where content is currently not objective, as reflected in the viral phenomenon of disputes between food content creators who exaggerate their assessments and content creators who base their assessments on honest results. The main problem faced by culinary marketing industry owners today is the decline in the quality of relationships between influencers and their followers, which will have an impact on low consumer purchasing interest. This study examines the influence of persona attributes consisting of similarity, inspiration, and level of enjoyment, as well as the credibility of influencers on relationship quality and purchase intent. The research method used was hypothesis testing and cross-sectional data, with respondents obtained through an online survey using a Likert scale to assess each item. The researchers gave 27 questions to each respondent. This study obtained 270 respondents who met the classification determined by the author. The minimum age studied by the author was 17 years old, as it was expected that respondents would be able to understand the role of social media. This study used the Stimulus-Organism-Response (S-O-R) method, which was very interesting to explore.